The Use of Red Shoot Ornamental Plants as Renewable Energy Fuel Cells for Electricity Generation - Rizky, Andri Nur Dewa; Nugraha, Faisal Cahya; Wulandari, Rindi (Indonesian Journal of Advanced Research, 2025)
This study examines the potential of red shoot plants (Syzygium oleina) to generate electricity using a Plant-Microbial Fuel Cell (P-MFC) with organic fertilizer variations of 25%, 50%, 75%, and 100%. The experiment, conducted on July 10–14, 2025, in Cirebon, used pots with humus soil, iron mesh anodes, and iron rod cathodes, measuring voltage and current every 60 minutes. Results showed a maximum voltage of ±1.70 V, current of ±1.04 A, and highest parallel power of ±0.374 mW. LEDs lit only at 75% and 100% fertilizer. Increasing fertilizer improved power output. In conclusion, red shoots can produce stable small-scale electricity and have potential as renewable energy, though electrode materials and system design need optimization for higher efficiency.